LRT skyline / Mohammad Danish Haikal Mohd Tamize - Mohd Tamize, Mohammad Danish Haikal (Universiti Teknologi MARA, Kedah, 2024)
An inventive double-decker light rail transit (LRT) system called LRT Skyline was created to meet the escalating needs of urban mobility. Through improvements in capacity, comfort, and efficiency, this project ushers in a new era of public transportation in densely populated cities. By optimising the use of available space, the double-decker design permits a notable increase in passenger capacity without requiring substantial infrastructural adjustments. The LRT Skyline boasts cutting-edge passenger amenities, energy-efficient propulsion, and cutting-edge safety measures. While the lower deck makes sure that everyone, even those with mobility problems, may easily enter and exit the aircraft, the top deck offers panoramic views that make for a distinctive and enjoyable travel experience. The LRT Skyline is also built with sustainability in mind; to reduce its negative effects on the environment, it uses eco-friendly materials and regenerative braking technology. The LRT Skyline boasts cutting-edge passenger amenities, energy-efficient propulsion, and cutting-edge safety measures. While the lower deck makes sure that everyone, even those with mobility problems, may easily enter and exit the aircraft, the top deck offers panoramic views that make for a distinctive and enjoyable travel experience. The LRT Skyline is also built with sustainability in mind; to reduce its negative effects on the environment, it uses eco-friendly materials and regenerative braking technology.